The position of the Algerian National press about the political Assassinations in tunisia: Farhat Hashad and Al-Hadi Shaker as a model )1952-1953( - ouabel, abdelaziz (The Algerian Historical Journal, 2026)
The activity of the national movement in Tunisia increased since the beginning of the fifties of the twentieth century by calling for the Tunisian issue to be presented in international forums. The reactions of the French authorities were violent, as they resorted to infernal methods, represented in exile, arrests, killing and assassinations of prominent elements in the Tunisian national movement with the aim of eliminating votes Demanding the independence of Tunisia, Habib Bourguiba and Monji Salim were arrested on January 18, 1952, then the unionist Farhat Hached was assassinated on December 5, 1952, and the militant Hedi Chaker was assassinated on September 13, 1953.